2021
DOI: 10.20525/ijrbs.v10i7.1369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of challenge-based and activity-based learning approaches on technical college students’ achievement, interest and retention in woodwork technology

Abstract: This study examines the effects of challenge-based and activity-based learning approaches on technical college students’ achievement, interest and retention in woodwork technology. A quasi-experimental research design was adopted. The study constituted a total number of 122 subjects, 63 for Challenge-based learning, while 59 were for activity-based learning. The study revealed that students who taught woodwork using the challenge-based learning instructional approach had a higher mean score than students taugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…If students believe that the activities are more challenging and that they can establish their own goals, receive feedback and praise about their improvement and effort, or receive clear expectations and hints to foster a deeper understating, they are more likely to engage in the activities and, in turn, improve their level of practical competence. These findings aligned with those indicating that perceived competence might be related to the learning process [ 42 , 44 , 45 ]. These studies suggested that the provision of choice and the promotion of active participation between students in CBL experiences might significantly improve learning and enhance their competence satisfaction, which might also be related to students’ engagement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…If students believe that the activities are more challenging and that they can establish their own goals, receive feedback and praise about their improvement and effort, or receive clear expectations and hints to foster a deeper understating, they are more likely to engage in the activities and, in turn, improve their level of practical competence. These findings aligned with those indicating that perceived competence might be related to the learning process [ 42 , 44 , 45 ]. These studies suggested that the provision of choice and the promotion of active participation between students in CBL experiences might significantly improve learning and enhance their competence satisfaction, which might also be related to students’ engagement.…”
Section: Discussionsupporting
confidence: 86%
“…As for the learning content, it should provide students with the opportunity to interact with one another. This educational framework has been investigated in different disciplines, with an increasing emphasis in the fields of engineering and medicine but few studies in the field of PE [ 42 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in keeping with existing studies that suggest that perceived competence might be related to the learning process. [27][28][29] These authors pointed out that the promotion of active participation through the use of technologies, and the provision of choice in the form of a challenge-based learning methodology might improve significant learning and, in turn, strengthen their perceptions of competence, which may be also related to students' engagement. Therefore, the fact that this pedagogical approach (challenge-based learning) fosters the clear establishment of evaluation processes or the provision of optimal challenge, [30][31][32] might explain how this methodology is more likely to promote feelings of competence among students than the TT methodology.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] In this study, it is plausible to think that the provision of optimal challenges and clear guidance might make students more likely to be active, participate and follow the teachers' instructions or put more effort into their tasks. Given the positive association between technologies, the challenge-based learning approach and learning outcomes, 27,28 it is possible to highlight the potential of ICT for improving educational processes.…”
Section: Discussionmentioning
confidence: 99%